Entrepreneurship as a result of research: a pending task in Colombia (Encuentros, 2021)
This article reviews academic entrepreneurship; and the transfer of knowledge and technology through strategies to market research, development and innovation results from universities in Colombia. It approached technology-based companies and actors of the National Science and Technology System; data from Colciencias, and “Spin-Off” Colombia. It presents quantitative results on secondary sources, processed in IBM SPSS. 3% of the reports are products of technological development; in higher education institutions, the entrepreneurial products are the 0.00095% of the all products. The commitment of the university with its entrepreneurial mission is incipient: it is necessary to deepen to know the model of creation of companies based on research, adequate for Colombia.